Anatomical and morphophysiological leaf blade traits of Panicum maximum genotypes - Gomes, Roberta Alves (2011)
The objective of this work was to evaluate anatomical and morphophysiological traits of the leaf blade of Panicum maximum genotypes, and to determine which ones favor an early discrimination of promising genotypes for nutritive value. The experiment was carried out in Dourados, MS, Brazil, between January 2006 and November 2007. Twenty-three P. maximum genotypes, which were pre-selected from the Embrapa Gado de Corte breeding program, were evaluated. The experimental design was a randomized block, with three replicates. Twenty-seven anatomical and morphophysiological leaf blade traits were evaluated in each genotype. For each trait, the results were grouped by the Scott-Knott test. The relative contribution of the traits to genetic divergence was determined by the Singh method. The traits that best discriminated the genotypes were the proportion – in the leaf blade cross-sections – of upper, lower, and upper + lower epidermis, and of mesofile and vascular bundles + sclerenchyma. Specific leaf area, leaf area, and leaf blade length were the morphophysiological traits that showed higher contribution to genotype discrimination; however, their relative importance was much lower than that of the anatomical traits. The proportion of parenchymatic bundle sheath cells and blade width show phenotypic instability.